The effect of multi-purpose tree digesta on in vitro gas production from Napier grass or neutral-detergent fibre - Nsahlai, I.V.; Umunna, N.N.; Negassa, D. (Wiley, 1995)
This study evaluated differences in gas production of leaves gathered from a range of multi-purpose trees (MPT) of Acacia, Cajanus, Chamaecytisus, Leucaena, Ricinus, Sesbania and Veronia species and the effect of their digesta (obtained by fermenting MPTs for 24h) on gas production of Napier grass *Pennisetum purpureum, Schumach)(Napier GP) and netural-detergent givre (NDF) extracted from Napier grass (NDF GP). Fresh samples of MPTs were incubated in triplicate or quintuplicate in a medium prepared from sieved rumen liquor harvested from two rumen-fistulated cows fed native pasture hay ad libitum and 2.0 kg cottonseed cake per head day-1. There was a wide variation in the volume of gas produced by the MPTs. With the exception of the leaves of R communis (castor oil plant) and L pallida (14189), the MPTs produced less (P<0.05) gas than Napier grass. Sesbania goetzei (1279 and 15007), and C cajan (12842) produced gas at a slower (P<0.05) rate than Napier grass. The digesta of MPTs induced rates of Napier GP that ranged from 0.63 to 0.83 the value obtained with the Napier grass digesta. With the exception of S Sesban (10865), C palmensis and R communis leaves, the MPT digesta induced Napier GP similar to or slightly higher than the Napier grass digesta. The digesta of S sesban (10805), A siberiana (pods), C cajan (11443, 12842) and C palmensis depressed the cumulative extent of NDF GP relative to Napier grass digesta. The MPT digesta prolonged the lag phase that precedes NDF GThe results are discussed in relation to the effect of MPT digesta on aspects of cell wall fermentation and are corroborated with results obtained in vivo. It was concluded that the major effect of antifermentation factors in the MPTs would be manifested in vitro in prologed lag phase preceding the onset of NDF GP and inslowed rate of Napier GP.